2022
DOI: 10.1038/s41420-022-01102-5
|View full text |Cite
|
Sign up to set email alerts
|

Box C/D snoRNA SNORD89 influences the occurrence and development of endometrial cancer through 2’-O-methylation modification of Bim

Abstract: The small nucleolar RNA (snoRNA) is a type of small non-coding RNA widely distributed in the nucleoli of eukaryotic cells, promoting cancer development. The aim of this study was to assess box C/D snoRNA 89 (SNORD89) dysregulations in endometrial cancer. According to the TCGA database as well as the International Federation of Gynecology and Obstetrics (FIGO), higher SNORD89 expression is found in endometrial cancer tissues. In addition, the SNORD89 expression level was higher in endometrial carcinoma with lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…18 SNORD89 regulates 2′-Omethylation of Bim mRNA, leading to reduced Bim protein levels by inhibiting translation. 19 These results are consistent with a previous study showing that 2′-O-methylation of synthetic mRNAs interferes with translation elongation and induces site-specific ribosome stalling in vitro. 20 In contrast, SNORD104 enhances PARP1 mRNA stability and translation in endometrial cancer cells by installing 2′-O-methylation on PARP1 mRNA, thereby promoting tumor growth.…”
Section: Rna-guided 2′-o-methylationsupporting
confidence: 93%
See 1 more Smart Citation
“…18 SNORD89 regulates 2′-Omethylation of Bim mRNA, leading to reduced Bim protein levels by inhibiting translation. 19 These results are consistent with a previous study showing that 2′-O-methylation of synthetic mRNAs interferes with translation elongation and induces site-specific ribosome stalling in vitro. 20 In contrast, SNORD104 enhances PARP1 mRNA stability and translation in endometrial cancer cells by installing 2′-O-methylation on PARP1 mRNA, thereby promoting tumor growth.…”
Section: Rna-guided 2′-o-methylationsupporting
confidence: 93%
“…For instance, Snord32a and Snord51 cooperatively 2′- O -methylate Pxdn mRNA in mice, stabilizing its mRNA level but inhibiting its translation . SNORD89 regulates 2′- O -methylation of Bim mRNA, leading to reduced Bim protein levels by inhibiting translation . These results are consistent with a previous study showing that 2′- O -methylation of synthetic mRNAs interferes with translation elongation and induces site-specific ribosome stalling in vitro .…”
Section: The Biogenesis and Functions Of Rna-guided Rna Modificationssupporting
confidence: 88%
“…It has been reported that SNORA71A promotes breast cancer metastasis by stabilizing ROCK2 mRNA through binding with the G3BP protein [ 11 ]. SNORD89 upregulation in endometrial cancer inhibits Bim and suppresses the apoptosis of endometrial cancer cells by binding to fibrillarin (Fbl) [ 6 ]. SNORD17 facilitates hepatocellular carcinoma (HCC) progression by anchoring nucleophosmin 1 (NPM1) and MYB binding protein 1a (MYBBP1A) in the nucleolus, leading to p53 inhibition [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated the role of snoRNAs in the pathology of various cancers. As an epigenetic regulator, abnormally expressed snoRNAs can activate or inhibit cancer-related signalling pathways by regulating target genes and altering cell biological behaviors, thereby regulating the proliferation, self-renewal and metastasis of cancer cells and affecting tumorigenesis [ 6 8 ]. For example, SNORD33, SNORD66 and SNORD76 are highly expressed in the tissues and plasma of lung cancer patients and can be used as potential prognostic markers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In endometrial cancer, the box C/D snoRNA SNORD89 expression level is higher in patients with lymph node metastasis than those without lymph node involvement. Furthermore, SNORD89 overexpression promotes cell migration and inhibits BIM mRNA translation through higher activity of 2 Ome, thus dysregulating the Bim/Bcl2/Bax signalling pathway leading also to apoptosis inhibition [100]. In breast cancer, SNORA71A is highly expressed in metastatic breast cancer tissues compared to non-metastatic samples.…”
Section: Mirna and Snorna Expression In Cancer Cells And Their Roles ...mentioning
confidence: 99%